ENHANCE PROMOTION STRATEGIES CV UTERO GO INTERNATIONAL - Albertus Eka; Roberto J Albuja Solis; Lea Voight; Nuriah Nuriah; Swe Swe Win; Ashknani Kawther (AIBPM Publisher, 2017)
With ongoing globalization, many business opportunities emerge all over the world. Operating business in one single country means to fail at exploiting additional profit from exporting one’s product or service globally. The following report will analyst the business operations of the company Utero, a creative design agency, responsible for brand, design and consultant services and located in Indonesia. As the company is already very successful in their country of origin, they should start exporting their services to other countries, to grow and yield additional profit. In order to do so, we will construct a marketing plan for Utero, based on a thorough analysis of the company’s background, its vision, mission and organizational structure. Also, we are going to assess the readiness of the company to do international marketing. Finally, we are going to give advice on how to successfully develop and implement international marketing, to enter markets all over the world. We found, that Utero should implement different marketing strategies, such as publishing a video of the firm online to increase brand awareness and spread it on social media networks such as Facebook. Other possible ideas would be to create a company-based Facebook page or create advertisement that will be displayed on YouTube. In general, our report aims at leading the company Utero on a successful path for further development and we believe that our proposed marketing plan will enable the company to significantly expand their business.